2023
DOI: 10.1021/jacsau.3c00039
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Peniroquesine Biosynthetic Pathway by Retro-Biosynthetic Theoretical Analysis: Ring Strain Controls the Unique Carbocation Rearrangement Cascade

Abstract: Peniroquesine, a sesterterpenoid featuring a unique 5/6/5/6/5 fused pentacyclic ring system, has been known for a long time, but its biosynthetic pathway/mechanism remains elusive. Based on isotopic labeling experiments, a plausible biosynthetic pathway to peniroquesines A–C and their derivatives was recently proposed, in which the characteristic peniroquesine-type 5/6/5/6/5 pentacyclic skeleton is synthesized from geranyl–farnesyl pyrophosphate (GFPP) via a complex concerted A/B/C-ring formation, repeated rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…All calculations were carried out at the M06-2X level using Gaussian and GRRM programs. M06-2X was selected because of its accuracy in calculating reaction energies for organic polysulfide compounds and its proven track record in reaction mechanism analysis of natural products. Our initial calculations strongly suggested that the spontaneous desulfurization reaction of 3 does not occur kinetically under neutral conditions. However, under basic conditions, the Path 1-type multistep degradation of the disulfide moiety proceeds smoothly at ambient temperature with reasonable activation energies and large overall exothermicity: deprotonation of phenolic OH of 3 initiates a multistep anion-relay cascade leading to 4 .…”
mentioning
confidence: 99%
“…All calculations were carried out at the M06-2X level using Gaussian and GRRM programs. M06-2X was selected because of its accuracy in calculating reaction energies for organic polysulfide compounds and its proven track record in reaction mechanism analysis of natural products. Our initial calculations strongly suggested that the spontaneous desulfurization reaction of 3 does not occur kinetically under neutral conditions. However, under basic conditions, the Path 1-type multistep degradation of the disulfide moiety proceeds smoothly at ambient temperature with reasonable activation energies and large overall exothermicity: deprotonation of phenolic OH of 3 initiates a multistep anion-relay cascade leading to 4 .…”
mentioning
confidence: 99%
“…Single-point energies were calculated at the mPW1PW91/6-31+G(d,p) level based on the optimized structure by using the M06-2X method. The utility of relative Gibbs free energies (G rel ) based on single-point energy at the mPW1PW91 level has been previously validated for a wide variety of terpene-forming reactions [ 22 , 41 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, three nortriterpenes from the roots of Ziziphus mauritiana, zizimauritic acids A (120), B (121), and C (122), with a unique A-nor-E-seco spiro-lactone ceanothane-type triterpene skeleton, were identified. These compounds displayed cytotoxicity, with IC 50 values ranging from 5.05 to 11.94 µg/mL, and compounds 120 and 122 inhibited the growth of Staphylococcus aureus, with IC 50 values of 2.17 and 12.79 µg/mL, respectively [86].…”
Section: A-norsteroids and Triterpenoids Derived From Terrestrial Sou...mentioning
confidence: 99%
“…Roquefornine A (177), a sesterterpenoid featuring an unprecedented 5/6/5/5/6-mem- Roquefornine A (177), a sesterterpenoid featuring an unprecedented 5/6/5/5/6membered pentacyclic system, was characterized from the fungus Penicillium roqueforti YJ-14 [119]. Additionally, other sesterterpenes, peniroquesines A-C (178-180), with a unique 5-6-5-6-5-fused pentacyclic ring system, were isolated from the same fungus through solid fermentation [120,121].…”
Section: A-norsteroids and Triterpenoids Derived From Terrestrial Sou...mentioning
confidence: 99%